2007
DOI: 10.1159/000104091
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure-Independent Effect of Long-Term Treatment with the Soluble Heme-Independent Guanylyl Cyclase Activator HMR1766 on Progression in a Model of Noninflammatory Chronic Renal Damage

Abstract: Nitric oxide formation is impaired in chronic renal failure. The renoprotective effects of a nonhypotensive dose of HMR1766, a direct activator of the heme enzyme soluble guanylyl cyclase was studied in comparison to an ACE-i in the remnant kidney model. Male Sprague-Dawley rats were subtotally nephrectomized (SNX) or sham operated (sham) and left untreated or started on treatment with HMR1766 or ACE-i in non-hypotensive doses. BP, albumin excretion and parameters of renal damage were analyzed. After a 12-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Notably, this was achieved at doses of BI 703704 (0.3, 1, and 3 mg/kg) that did not significantly reduce MAP. This is consistent with a previous report indicating that treatment with the sGC activator HMR1766 can reduce urinary albumin excretion in the rat 5/6 nephrectomy model of chronic renal failure without affecting blood pressure (Benz et al, 2007). Thus, although BI 703704 is capable of reducing blood pressure, significant hemodynamic effects are not required to induce robust proteinuria reductions in ZSF1 rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, this was achieved at doses of BI 703704 (0.3, 1, and 3 mg/kg) that did not significantly reduce MAP. This is consistent with a previous report indicating that treatment with the sGC activator HMR1766 can reduce urinary albumin excretion in the rat 5/6 nephrectomy model of chronic renal failure without affecting blood pressure (Benz et al, 2007). Thus, although BI 703704 is capable of reducing blood pressure, significant hemodynamic effects are not required to induce robust proteinuria reductions in ZSF1 rats.…”
Section: Discussionsupporting
confidence: 93%
“…* ,# Significant P , 0.05 versus vehicle and enalapril, respectively, using one-way analysis of variance. rat 5/6 nephrectomy model of chronic renal failure (Kalk et al, 2006;Benz et al, 2007). This model is characterized by surgically-induced impaired renal function, but lacks the diabetic milieu and its impact on renal molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Dahl rats fed a high-salt diet (JP Stasch et al, unpublished). In a low-NO/high-renin rat model of hypertension, vericiguat reduced right and left ventricle hypertrophy and mortality, and showed a positive effect on grading of kidney changes, and the incidence and severity of myocardial lesions [49][50][51][52][53]54 ]. The potentially beneficial effects of vericiguat on cardiac function are supported by the findings from recently completed phase I studies, which found that this agent leads to improvement in important cardiologic parameters, including: cardiac output/index, systemic vascular resistance, and stroke volume [49].…”
Section: [27]mentioning
confidence: 99%
“…Inasmuch as impaired autoregulation provides a risk factor for chronic renal failure, particularly in combination with hypertension (5), the findings also suggest safety with regard to chronic renal failure. In addition, cinaciguat and the structurally unrelated sGC activator ataciguat (HMR1766) have been shown to play a beneficial role in chronic kidney disease (4,35), presumably due to nonvascular effects ascribed to NO and cGMP on renal inflammation, fibrosis, and glomerulosclerosis (10,36,63).…”
Section: Perspectivesmentioning
confidence: 99%